Predictors of low dental service utilization among school children in Mekelle, Northern Ethiopia: a cross-sectional study - Hayat Maeruf Mohammed; Mihret-ab Mehari; Akeza Awealom Asgedom (BMC, 2023)
Abstract Background Dental service utilization is important for maintaining and enhancing children's oral health status. However, there is paucity of information regarding dental service utilization and factors affecting it among school aged children in Ethiopia. Objectives The purpose of this study was to determine the dental service utilization and associated factors among school aged children (6-15) years in Mekelle city, Northern Ethiopia. Methods A school-based cross-sectional study was conducted in Mekelle city of Northern Ethiopia from January 2016 to June 2016. A multi-stage sampling method was used to select 405 school children. A modified World Health Organization oral health assessment form for children was used to collect data. Univariate and multivariable logistic regressions with 95% CI were used to test the association between past-year dental service utilization, as an outcome variable, and parental socio-demographic, and child characteristics as independent variables. Results A total of 398 school children participated in the study. The overall dental service utilization among these children was (10.6%), 95% Confidence Interval (CI) (7.5%, 13.6%). In multivariable logistic regression analysis, maternal educational status (illiterate versus college and above (adjusted odds ratio (AOR) 0.13, 95% CI 0.01, 0.93)), higher monthly income (AOR 11.69, 95% CI 1.19, 114.61)), and having dental pain (AOR 50.8, 95% CI 17.8, 145.17)) were significantly associated with past year dental service utilization. Conclusion Our findings showed that a small proportion of the study population visited a dentist in the past year. Maternal educational status, monthly income, and dental pain were associated with past year dental service utilization. Oral health education programs focusing on dental service utilization targeting school children are crucial.